Are refugees applying to child and adolescent psychiatry departments only to obtain a disability report? The experience of a department in a Turkish city on the Syrian border (Annals of Medical Research, 2021)
Aim: Children and adolescents are the most affected by wars. They are also at higher risk for psychiatric disorders. However, as in all disadvantaged groups, the reasons for applying to psychiatry departments in refugees may differ from the local population. So we aimed to investigate reasons for applying to psychiatry department, the sociodemographic characteristics, presence of psychopathologies, prescriptions and treatment compliance of child and adolescent Syrian refugees.Materials and Methods: This research comprises an outpatient clinical sample of 400 refugee patients. The data was obtained by retrospectively examining the records of Syrian refugee patients aged between 0 and 18 years old who applied to Mardin State Hospital Child and Adolescent Psychiatry Department between May 2018 and May 2019. The sociodemographic characteristics of the cases, their psychiatric diagnoses according to DSM-5, medicines, and their continuation to psychiatric controls were evaluated.Results: 59% (235) applied to the department for treatment of psychiatric symptoms and 41% (165) applied to obtain a disability report. The mean age of refugees included in the study was 8.1 ± 4.7, out of which 231 were boys (58%) and 169 were girls (42%). The two most common diagnoses were Intellectual Disabilities: n=46 (19%) and Trauma and Stressor Related Disorders: n=39 (17%). Only 27% of patients showed compliance with the offered treatment. The most used medications were antipsychotics (41.17%) and antidepressants (38.16%).Conclusion: In our sample psychopathology rates were high and treatment compliance was low. In addition, the application rate for the disability report was quite high. As a result protective and therapeutic strategies should be implemented to address these issues and awareness should be increased for psychiatric disorders.
Keywords: Children; refugee; Syria; trauma; treatment compliance